Management Rights in Underground Post Application of Law Number 11 of 2020 Concerning Copyright and Implementation Regulations - Karina, Ida Ayu Aditya; Koeswahyono, Imam; Anggraini, Erna (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This thesis is entitled "Management Rights in Underground Spaces After the Enactment of Law Number 11 the Year 2020 concerning Job Creation and Implementing Regulations" with 2 (two) main problems, namely, (1) How is the Legal Certainty regarding the Granting of Permits and Limitations on the Use of Utilization? Basement? What is the legal status of basements after the enactment of Law Number 11 of 2020 concerning Job Creation and its Implementing Regulations? This research is a type of legal research with normative research methods. Besides, this research uses a statutory approach and a conceptual approach. The results of this thesis research indicate that the legal certainty of granting permits in terms of the use of underground spaces is based on Law no. 11 of 2020 concerning Job Creation, Article 146 Land or space formed in the upper and/or underground space and used for certain activities may be granted building use rights, use rights or management rights, in this case granting rights to the utilization of the underground space. based on the Basic Agrarian Law. Restrictions on the use of the authority of those who use it are limited by the existence of procedures that must be met in terms of the use of basements and the depth limit stipulated in the Implementing Regulation of the Employment Creation Act, Article 74, namely with a height limit according to the basic coefficient of the building and the floor of the building as well as a depth limit of 30. meters from the surface of the land that can be reached by the process of registering rights through the granting of rights that take into account/consider the holders of land rights under and/or above it. The arrangement for the acquisition of the right to use the basement is regulated in Government Regulation Number 18 of 2021 concerning Management Rights, Land Rights, Flat Units, and Land Registration Article 77, namely, Upper Land or Ground Spaces may be granted Management Rights, Building Use Rights, or Right of Use after the Upper Ground or Underground Space is utilized. The granting of rights is granted by a decision on granting rights by the Minister. The regulation regarding land rights is guided by the Basic Agrarian Law.